The Impact of Technology on Anxiety Management in University Students - Paula Puente-Torre; Vanesa Delgado-Benito; Sonia Rodríguez-Cano; Miguel Ángel García-Delgado (Behavioral Sciences)
Anxiety is one of the main disorders affecting university students, partly due to the current predominant pace of life and the competitive environment of the university. In this sense, the use of technology to reduce anxiety is one of the main tools available to university students. In order to analyze the current situation of the university population with respect to anxiety levels, both state anxiety and risk anxiety, the State-Trait Anxiety Inventory Questionnaire (STAI) was used and applied to a sample of four hundred and fifty students at the University of Burgos, ensuring the representativeness of this population by means of non-probabilistic sampling. Descriptive research has been carried out to determine the levels of anxiety of students at the University of Burgos. Likewise, the benefits of different studies on the application of technology to reduce anxiety are presented, as well as the applications most used by university students. In general terms, we can consider that the implementation of mindfulness techniques through emerging technologies promotes a reduction in anxiety levels among the university population. However, it is necessary to clarify that the data presented only indicate a correlation, not a relationship of cause and effect. Finally, various proposals for improvement and expansion of the research carried out are offered.